(untitled) (Proceedings of International Conference on Special Education, 2015)
Every year Thai students with disabilities are entering to the United States in order to study. Some of them study in specific university, such as Gallaudet University. At the same time, there are a large number of Thai students with disabilities are attending schools with the mainstream. They might need accommodation and service to facilitate their academic performance and daily life while studying abroad. Hence, Royal Thai government plays a key role to support and assist Thai students with disabilities. School and a professor are also important because they have to be eager to provide what Thai students with disabilities need. Ultimately, Thai students with disabilities are able to determine what ability they have and what they need to ease and improve their academic performance. . Self-determination skills are essential for Thai students with disabilities to receive services and accommodation from Royal Thai government, school, and a professor. This study aims to investigate how Thai students with disabilities understand and use the self-determination skills effectively. Another reason for the survey is to use the information for future Thai students with disabilities. The survey takes about 5 minutes and the results will be used for future Thai students with disabilities how to promote their self-determination to receive services and accommodations to facilitate their academic and social performance There are a few respondents who completed the online survey. The findings indicate that most of Thai students greatly understand and use self-determination skills with Royal Thai government, school, and a professor. Thai students with disabilities also report their positive satisfaction of the services and accommodations. Significantly, culture differences are discussed